Dis/connecting Islam and terror: the 'Open Letter to Al-Baghdadi' and the pitfalls of condemning ISIS on Islamic grounds - Sing, Manfred (Journal of religious and political practice, 2016)
When Muslim individuals or groups perpetrate acts of violence, Muslim scholars are routinely required to condemn the 'misuse' of Quranic verses, and scholars of Islamic studies have to 'explain' the distant relation between classical jihad and modern terrorism. Most critics of an organization like the 'Islamic State' (ISIS) refute a direct link between its violence and Islam. However, they paradoxically take this link seriously enough to discuss it in detail or discard it entirely, by attributing it to an 'Islamophobic' perception of Islam. As misuse is still a kind of use and distance a kind of closeness, these experts risk reconstructing the connection that most of them wish to undermine because their criticism, by aiming at ISIS or 'Islamophobia,' still conjures up an Islamic imaginary. The article draws attention to the pitfalls in talking about so-called 'Islamic terrorism' and sheds a light on the under-researched politics of condemnation, in which Muslims are routinely called upon to engage. A case in point is the 'Open Letter to al-Baghdadi,' published by 126 religious scholars in 2014, which condemned ISIS on religious grounds. The author argues that such a condemnation contributes to an asymmetrical perception of Islam and an ideological understanding of terrorism. It reiterates truncated understandings about the root causes of political violence, while failing to address the thorny issue surrounding legitimate forms of violence. The main problem bedeviling the critics of Islamically justified terrorism is the ambiguous nature of a terror organization like ISIS, whose communication strategy forcefully targets Muslim as well as non-Muslim audiences and their attempts to vindicate or blame Islam.